Analisis Rasio Likuiditas Dan Profitabilitas Terhadap Kinerja Keuangan Pada Rumah Sakit Umum Bunda Jakarta Tahun 2021-2024 - Dini Hapsari (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to determine the effect of liquidity ratios and profitability ratios on the financial performance of Bunda General Hospital Jakarta. The population and research sample are the last 4 (four) years of congratulatory financial reports in the 2021-2024 period. The sample technique used in this study uses non-probability sampling techniques, namely purposive sampling techniques. The research method used is descriptive quantitative. The partial research results on the liquidity ratio variable through the Current Ratio (X1) analysis show that there is no significant effect of liquidity ratios on financial performance at Bunda General Hospital Jakarta in 2021-2024 partially. In the profitability ratio variable through the analysis of Net Profit Margin (X2), it shows that there is no significant effect of profitability ratio on financial performance at Bunda General Hospital Jakarta in 2021-2024 partially. Simultaneously, it shows that there is an effect of the effect of liquidity and profitability ratios on financial performance at Bunda General Hospital Jakarta in 2021-2024 simultaneously.